MR imaging in patients with suspected liver metastases: value of liver-specific contrast agent Gd-EOB-DTPA - Zech, Christoph J; Herrmann, Karin A; Reiser, Maximilian F; Schoenberg, Stefan O (Magnetic resonance in medical sciences, 2007)
The appropriate staging of malignant tumors is increasingly important as new therapeutic strategies develop. Because metastatic involvement of the liver in extrahepatic malignant disease may significantly change therapeutic approach, it is important to rule out such involvement with high confidence. Moreover, the differentiation between incidental benign lesions, such as hemangioma, focal nodular hyperplasia (FNH), or adenoma, is of high interest. Magnetic resonance (MR) imaging has proved reliable for diagnostic work-up of the liver. Liver-specific contrast agents have been especially helpful in detecting and precisely characterizing focal liver lesions, but the use of these agents has been limited because it has not been possible to perform both proper vascular phase and liver-specific phase within a reasonable time frame and in a single examination after a single injection of contrast agent. However, the hepatobiliary contrast agent gadolinium-ethoxybenzyl (Gd-EOB)-DTPA now allows combined dynamic imaging and hepatocyte-specific imaging in one examination. Gd-EOB-DTPA can be injected as a bolus and shows the enhancement characteristics and vascularity of liver lesions. In the delayed phase, which is acquired most appropriately 20 min after injection, Gd-EOB-DTPA is taken up selectively by functioning hepatocytes. Thus, malignant liver lesions, e.g. metastases, are spared from contrast uptake of the surrounding liver parenchyma. These lesions are hypointense in contrast to the surrounding bright liver. We review the current literature and present a practical approach to Gd-EOB-enhanced MR imaging using imaging examples of patients with liver metastases.